Italy : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper describes stylized facts, institutions, and directions for reform in the Italian labor market. The paper examines developments in aggregate features of the labor market. It highlights that during the latest cyclical recovery, total employment has remained stagnant and the unemployment rate has not declined despite modest output growth. The paper examines different features of labor market developments from a longer-term perspective, reviewing developments in regional labor markets as well as the evolutions of employment shares and relative wages across sectors. The paper also describes the Italian social protection system.